Responsabilidad social corporativa y edadismo en el ámbito público-privado. Ibex-35 y Universidade de Vigo - Dra. Ana Belén FERNÁNDEZ SOUTO,Dra. Montserrat VÁZQUEZ GESTAL,Dr. Xaime FANDIÑO ALONSO (Fonseca, Journal of Communication, 2023)
The Sustainable Development Goals (SDGs) were accepted by the public and private sectors of the UN countries, which included them into their social policies and CSR strategies. In 2020, the WHO launched the Decade of Healthy Aging, calling attention to ageism and age discrimination against the group of older adults, a group that does not exist in the SDGs, which focuses on children and/or adults.